Anatomic variations of the lateral intercondylar ridge: Relationship to the anterior margin of the anterior cruciate ligament - Sachiyuki Tsukada (2018)
Background: The lateral intercondylar ridge (UR) has been recognized as an important landmark to create an appropriate femoral tunnel in single-bundle anterior cruciate ligament (ACL) reconstruction. However, because of variations in the distal part of the LIR or because the relationship between the LIR and the anterior margin of the ACL attachment has not been sufficiently clarified, the utility of the LIR for anatomic single- and double-bundle reconstruction remains controversial-Hypotheses: (1) There is a large degree of positional and dimensional variation in the LIR, specifically concerning the distal part (2) There may be significant differences between sexes in the LIR. (3) The anterior margin of the ACL attachment may be located anterior to the distal part of the UR. Study Design: Descriptive laboratory study-Methods: A total of 318 femora, which were collected with the donors' demographic data, were examined to determine anatomic variations of the UR. In addition, 20 cadaveric knees, in which the anterior margin was marked by radiopaque silicon markers, were examined with micro-computed tomography to evaluate the positional relationship between the UR and the anterior margin of the ACL attachment. Results: Although the LIR was identified in 94.0% of the 318 femora, the distal half of the LIR was not visible in 18.4% of these femora. Moreover, the LIR was located in an extremely anterior part of the lateral condyle surface in 8.8% in comparison with the common location, and in an extremely posterior part in 8.5%. The length-height ratio (69.9% in men, 63.6% in women) and the length between the inlet of the notch roof and the proximal part of the LIR (19.9 mm in men, 17.9 mm in women) were significantly greater in males than in females (P = .0028 and P < .0001, respectively). The anterior margin of the ACL attachment was commonly located anterior to the middle and distal part of the LIR, having the mean marker-ridge distance of 4.2 mm. Conclusion: There were large positional and dimensional variations in the LIR, specifically concerning the distal part. There are slight but significant differences between the male and female femora. The anterior margin of the ACL attachment is commonly located anterior to the middle and distal parts of the LIR. Clinical Relevance: Utility of the LIR as an osseous landmark for femoral tunnel creation is limited in anatomic reconstruction of the posterolateral bundle and anatomic single-bundle reconstruction. © 2014 The Author(s).